S2k-Leitlinie: Indikation Knieendoprothese: evidenz- und konsensbasierte Indikationsstellung in der Knie-Endoprothetik (EKIT-Knie) = The S2k guideline: indications for knee endoprosthesis : evidence and consent-based indications for total knee arthroplasty - Lützner, Jörg; Scharf, Hanns-Peter (Der Orthopäde, 2018)
Total knee arthroplasty (TKA) is one of the most frequent surgical procedures in orthopaedic surgery. Until now there have not been any standardized indication criteria, which might contribute to the large geographical differences in the frequency of TKA. This guideline aims to consent minimal requirements (main criteria), additional important aspects (minor criteria), as well as relative and absolute contraindications for TKA. The following main criteria have been consented: knee pain, radiological confirmation of osteoarthritis or osteonecrosis, inadequate response to conservative treatment, adverse impact of knee disease on the patient’s quality of life and the burden of suffering due to the knee disease. Relative contraindications have been consented as severe general disease with reduced life expectancy and a BMI ≥40; absolute contraindications are an active infection and if the patient is not able to undergo major surgery.
Gesehen am 23.07.2019